BEBERAPA IDENTITAS PADA GENERALISASI BARISAN FIBONACCI - Sri Melati; Mashadi '; Musraini M (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
We discuss some identities of generalized Fibonacci sequence, (un), which satisfies linear homogeneous recurrence relations of order two having a non-zero constant coefficient. Then given some matrices, we show that the n-power of these matrices provide some identities for Pni=0 u2i , unun+2, and Pni=0 unun+1. At the end we give generating functions for unun+1 and unun+2.